Development of ABCs Nursing Practice Guideline for Acute Hemorrhagic Stroke Patients in the Surgical Intensive Care Unit at Chiang Mai Neurological Hospital - Pongsavang, S; Anpunya, C; Poonsem, S (Journal of The Department of Medical Services, 2020)
This research and development study aimed to develop ABCs nursing practice guideline for acute hemorrhagic stroke patients in the surgical intensive care unit at Chiang Mai Neurological Hospital and to compare patients outcomes of the nursing practice and nurse practitioners’ satisfaction between the new practice and the conventional nursing practice. The sample consisted of 52 participants selected purposively. Participants were divided into 2 groups, with 26 subjects in each group. Data were collected from June to August 2019. The research instruments comprised of a manual evaluation form, a patients’ outcome of nursing practice form, and a satisfaction evaluation form. The validity and reliability of the research instruments were assessed by 3 experts prior to collecting data. The CVI values were 0.98 and 0.93, respectively. The reliability values as measured by Cronbach’s alpha coefficient were 0.96 and 0.83, respectively. Data were analyzed using frequency distribution, mean, percentage, and standard deviation, and compared using the exact probability test and the Mann-Whitney U Test. The study indicated that ABCs nursing practice guidelines for acute hemorrhagic stroke patients, developed by compiling nursing practice from empirical evidence, significantly reduced the duration of treatment in the intensive care unit (p < 0.05). Nurses were satisfied with the content and implementation at a statistically significant level (p < 0.05). The incidences of complications (increased intracranial pressure, cerebral edema, ventilator associated pneumonia, and aspiration) decreased compared to the former guideline from 34.6% to 23.1%. In conclusion, the application of ABCs nursing practice guideline for acute hemorrhagic stroke patients in the surgical intensive care unit can be useful to decrease patients’ length of stay and reduce the occurrence of preventable complications.